2016
DOI: 10.3758/s13421-016-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel metaphor comprehension: Semantic neighbourhood density interacts with concreteness

Abstract: Previous research suggests that metaphor comprehension is affected both by the concreteness of the topic and vehicle and their semantic neighbours (Kintsch, 2000;Xu, 2010). However, studies have yet to manipulate these 2 variables simultaneously. To that end, we composed novel metaphors manipulated on topic concreteness and semantic neighbourhood density (SND) of topic and vehicle. In Experiment 1, participants rated the metaphors on the suitability (e.g. sensibility) of their topic-vehicle pairings. Topic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
(72 reference statements)
4
17
0
3
Order By: Relevance
“…We saw some evidence of this in the interactions with familiarity in our data, where interference with the figurative meaning seemed to be negligible for the most familiar phrases. Comparing our results to other kinds of figurative language, Al-Azary and Buchanan (2017) found an interaction between concreteness and semantic neighbourhood density whereby only metaphorical topic-vehicle pairs from dense semantic neighbourhoods showed an effect of concreteness (more abstract topics were judged as more suitable, and understood more easily), while for less dense neighbourhood, concreteness had no effect. They also discuss their results in terms of a need to suppress irrelevant connections, which is more difficult for concrete topics with many near neighbours in semantic terms.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We saw some evidence of this in the interactions with familiarity in our data, where interference with the figurative meaning seemed to be negligible for the most familiar phrases. Comparing our results to other kinds of figurative language, Al-Azary and Buchanan (2017) found an interaction between concreteness and semantic neighbourhood density whereby only metaphorical topic-vehicle pairs from dense semantic neighbourhoods showed an effect of concreteness (more abstract topics were judged as more suitable, and understood more easily), while for less dense neighbourhood, concreteness had no effect. They also discuss their results in terms of a need to suppress irrelevant connections, which is more difficult for concrete topics with many near neighbours in semantic terms.…”
Section: Discussionsupporting
confidence: 55%
“…Alongside the contribution of semantic richness to the processing of single words, some researchers have also considered how this set of variables may influence processing of metaphors, where the meaning of a word is extended to encompass an additional, figurative meaning. Al-Azary and Buchanan (2017) found that both suitability judgments and online comprehensibility of metaphors were affected by concreteness (more abstract metaphors were facilitated) and semantic neighbourhood density (sparser neighbourhoods were facilitative). They also found an interaction between these two properties which they suggest may explain the variable results obtained for concreteness in previous metaphor studies (e.g.…”
Section: Take Down Policymentioning
confidence: 99%
“…One such computational model that has been proposed in regard of metaphor comprehension is the predication model ( Kintsch, 2000 , 2001 ; Chiappe and Chiappe, 2007 ; Al-Azary and Buchanan, 2017 ). This computational model assumes that metaphor comprehension is contingent on the activation of semantic neighborhoods in specific context ( Kintsch, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive computational model that can characterize the semantic processing between the topic and the vehicle of a metaphor is the predication model ( Kintsch, 2000 , 2001 , 2008 ; Kintsch and Bowles, 2002 ; Al-Azary and Buchanan, 2017 ). This model is composed of two components: a computational representation of the meanings of words and the application of these representations in computing a contextually appropriate interpretation of statements ( Kintsch, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation